2009
DOI: 10.1590/s0102-76382009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do pós-condicionamento isquêmico no tratamento da isquemia mesentérica: estudo experimental em ratos

Abstract: Avaliação do pós-condicionamento isquêmico no tratamento da isquemia mesentérica. Estudo experimental em ratosEvaluation of ischemic postconditioning effect on mesenteric ischemia treatment. Experimental study in rats Abstract Objective: To assess the preconditioning and postconditioning effect on intestinal mucosal lesions in rats undergone mesenteric ischemia and reperfusion procedure.Methods: Thirty Wistar rats were studied and divided into three groups: Group A, 10 rats undergone mesenteric ischemia (30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The protective mechanism of IPo in ischemia and reperfusion process is still not entirely clear, but there is evidence that IPo may be related to a significant decrease in the levels of malondialdehyde and products related to lipid peroxidation. These observations suggest a reduction in the production of ROS and less injury mediated by oxidants with IPo [ 1 - 9 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective mechanism of IPo in ischemia and reperfusion process is still not entirely clear, but there is evidence that IPo may be related to a significant decrease in the levels of malondialdehyde and products related to lipid peroxidation. These observations suggest a reduction in the production of ROS and less injury mediated by oxidants with IPo [ 1 - 9 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Several published experiments analyzed the effects of IPo in other organs and tissues, among them we can mention Darling et al [ 7 ] in which the IPo was able to minimize the area of myocardial infarction in rabbits; Tang et al [ 8 ] demonstrated the effectiveness of IPo in the prevention of coronary lesions resulting from the ischemia and reperfusion in rats, since the ischemia time did not exceed 45 minutes; Huang et al [ 3 ] have shown that the IPo was preventing tissue damage in the spinal cord of rats subjected to ischemia and reperfusion; Santos et al [ 9 ] showed that the ICRP and IPo was able to minimize tissue injury in the intestinal mucosa of rats undergoing ischemia and reperfusion process.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there have been studies demonstrating the efficacy of ischemic post-conditioning in various organs when subjected to ischemia and reperfusion [ 4 ] . Clearly, then came the questions about its protective effect also at a distance, the remote ischemic postconditioning (R-IPo).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [ 3 ] demonstrated that IPC were preventing tissue damage in the spinal cord of rats subjected to I/R. Santos et al [ 8 ] showed that the ischemic preconditioning and IPC were able to minimize the tissue injury in the intestines of rats subjected to mesenteric I/R process.…”
Section: Introductionmentioning
confidence: 99%